Barriers and facilitators to the quality use of essential medicines for maternal health in low-resource countries: An Ishikawa framework - Dan N. Tran; Lisa A. Bero (Edinburgh University Global Health Society, 2015)
Background An estimated 800 women die every day due to complications related to pregnancy or childbirth. Complications such as postpartum haemorrhage (PPH) and pre-eclampsia and eclampsia can be prevented by the appropriate use of essential medicines. The objective of this study was to identify the common barriers and facilitators to the availability and use of oxytocin, ergometrine, and magnesium sulfate (MgSO4) - essential medicines indicated for the prevention and treatment of PPH and pre-eclampsia and eclampsia. Methods We analyzed seven UNFPA/WHO reports published in 2008-2010. These reports summarized country-wide rapid assessments of access to and use of essential medicines for maternal health in Mongolia, Nepal, Laos, the Democratic People's Republic of Korea (DPRK), the Philippines, Vanuatu, and the Solomon Islands. We used a "fishbone" (Ishikawa) diagram as the analytic framework to identify facilitators and barriers at four health-system levels: government/regulatory, pharmaceutical supply, health facility, and health professional. Results Common facilitators to the quality use of essential medicines for maternal health were observed at the government/regulatory and health professional level. A majority of countries had these medicines listed in their essential medicines lists. Awareness of the medicines was generally high among health professionals. Common barriers were identified at all health-system levels. First, standard treatment guidelines were not available, updated, or standardized. Second, there was an inadequate capacity to forecast and procure medicines. Third, a required MgSO4 antidote was often not available and the storage conditions for oxytocin were deficient. Conclusions The "fishbone" Ishikawa diagram is a useful tool for describing the findings of rapid assessments of quality use of essential medicines for maternal health across countries. The facilitators and barriers identified should guide the development of tailored intervention programs to improve and expand the use of these life-saving medicines.